Application of Problem Based Learning (PBL) Model to Improve Problem Solving Skill from Critical Thinking Skill Students on Dynamic Fluid Materials - Selviyana Yana; Yusrizal Yusrizal; Ð. HÐ°ÓÑ–m; MuÒ»Ð°mmÐ°Ô Ð…ÑƒukrÑ–; Ð•ÓÑ–Ñ•Ð° Ð•ÓÑ–Ñ•Ð° (Jurnal Penelitian Pendidikan IPA, 2022)
The ability of students to solve problems is one of the benchmarks for the success of student learning. The increasing ability of students to be able to solve problems in learning is largely determined by the thinking skills they have. One of them is critical thinking skills. However, in reality, the problem solving skills of students at SMAN 1 Tapaktuan are still relatively low. The purpose of this study was to determine the application of the Problem Based Learning (PBL) model in improving the problem solving skills of students on dynamic fluid materials at SMAN 1 Tapaktuan and to determine the improvement of problem solving skills of students reviewed. of critical thinking skills on dynamic fluid material at SMAN 1 Tapaktuan by using the Problem Based Learning (PBL). The type of research used in this study is a quantitative approach with a Quasi Experimental Design method. The selected shape is Non-equivalent Control Group Design. The instrument used in this research is a test of problem solving skills and a test of critical thinking skills. The results of the implementation of the Problem Based Learning (PBL) model show that the increase in problem-solving skills in the experimental class is higher than the control class as seen from the N-gain of the two classes, namely the experimental class is in the high category (0.9) and the control class is in the medium category ( 0.6), and the improvement of problem solving skills in terms of students' critical thinking skills shows that for each indicator of problem solving skills the experimental class is greater than the control class.